Wide-field LOFAR imaging of the field around the double-double radio galaxy B1834+620: A fresh view on a restarted AGN and doubeltjes - Orru, E.; Van Velzen, S.; Pizzo, R.; Yatawatta, S.; Paladino, R.; Iacobelli, M.; Murgia, M.; Falcke, H.; Morganti, R.; De Bruyn, A.; Ferrari, C.; Anderson, J.; et al. (EDP Sciences, 2015)
The existence of double-double radio galaxies (DDRGs) is evidence for recurrent jet activity in active galactic nuclei (AGN), as expected from standard accretion models. A detailed study of these rare sources provides new perspectives for investigating the AGN duty cycle, AGN-galaxy feedback, and accretion mechanisms. Large catalogues of radio sources, on the other hand, provide statistical information about the evolution of the radio-loud AGN population out to high redshifts. Aims. Using wide-field imaging with the LOFAR telescope, we study both a well-known DDRG as well as a large number of radio sources in the field of view. Methods. We present a high resolution image of the DDRG B1834+620 obtained at 144 MHz using LOFAR commissioning data. Our image covers about 100 square degrees and contains over 1000 sources. Results. The four components of the DDRG B1834+620 have been resolved for the first time at 144 MHz. Inner lobes were found to point towards the direction of the outer lobes, unlike standard FR II sources. Polarized emission was detected at +60 rad m-2 in the northern outer lobe. The high spatial resolution allows the identification of a large number of small double-lobed radio sources; roughly 10% of all sources in the field are doubles with a separation smaller than 1'. Conclusions. The spectral fit of the four components is consistent with a scenario in which the outer lobes are still active or the jets recently switched off, while emission of the inner lobes is the result of a mix-up of new and old jet activity. From the presence of the newly extended features in the inner lobes of the DDRG, we can infer that the mechanism responsible for their formation is the bow shock that is driven by the newly launched jet. We find that the density of the small doubles exceeds the density of FR II sources with similar properties at 1.4 GHz, but this difference becomes smaller for low flux densities. Finally, we show that the significant challenges of wide-field imaging (e.g., time and frequency variation of the beam, directional dependent calibration errors) can be solved using LOFAR commissioning data, thus demonstrating the potential of the full LOFAR telescope to discover millions of powerful AGN at redshift z ~ 1.